Optimizing the Role of Mosques in Supporting the Implementation of Sustainable Development Goals (SDGs) to Improve the Mental Health of Generation Z in Mataram City: A Conceptual Research - Jamaludin, Jamaludin (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
Sustainable Development Goals (SDGs) are world steps that specifically emphasize efforts to improve people's welfare and health. However, generation Z in the digital era and urbanization faces increasingly complex mental health problems. Various changes and forms of evolution of technological development are not in line and run in harmony with the development of people's lives, in this conceptual research effort to combine various literature that connects the role of mosques in supporting mental health with SDGs goals related to welfare and health. Factors such as academic pressure, social media distractions, and lack of social support are significant mental health problems among generation Z. This research aims to develop the concept of optimizing the role of mosques as a key factor in achieving SDGs related to the mental health of generation Z in the city Mataram. The SDGs specifically emphasize efforts to improve people's welfare and health. This research concept illustrates how mosques can become centers that play an important role in solving SDGs problems and at the same time improving the mental health of generation Z. This includes programs in mosques that support counseling, education on religious values, social skills training, and mental health promotion . In addition, this research highlights the importance of collaboration between mosques, educational institutions, government and community organizations to create a strong ecosystem in improving the mental health of generation Z. By combining resources and knowledge, this concept aims to strengthen efforts towards a healthy and prosperous life. in line with the SDGs. The results of this conceptual research are concepts that provide a theoretical basis for designing integrated generation Z mental health prevention and intervention strategies in the context of the SDGs. This research encourages further attention and concrete steps in optimizing the role of mosques in achieving SDGs goals related to the mental health and welfare of generation Z in Mataram City.